Techniques for Incorporating Folklore into a Literary Text (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
this article discusses the methods of including folklore in a literary text on the example of a folklore word in literature; folklore "blotches" in the literary text. As well as the lyrical situation in folklore and literature.